Pemberdayaan Masyarakat Melalui Pengembangan Produksi Kopi sebagai Alternatif Usaha bagi UMKM di Kecamatan Sukorejo Kabupaten Kendal - Zora Alainashani; Triana Syifa; Syamsul Ma’arif; Tutik Wijayanti (Yayasan Al-Afif, 2025)
The background of this study lies in the branding of Sukorejo coffee, which is still limited to local markets and has not consistently highlighted its flavour profile as a key selling point. Critically, this reflects a particular challenge in creating added value at the level of MSMEs and farmers, thus requiring interventions focused on improving processing quality as well as implementing targeted promotional strategies. This community service activity aims to enchance the knowledge and capacity of the Sukorejo community in coffee processing practices, particularly in the stages of processing, marketing, and strengthening local coffee branding as a flagship product by MSME actors in Sukorejo District, Kendal Regerency. The object of this study is coffee MSME in Sukorejo District. The research method employed is a descriptive qualitative approach intended to provide a detailed account of the community empowerment process in coffee production and roasting in Sukorejo District. The results of this program indicate a strategic direction for the future development of Sukorejo coffee, namely the need for follow-up assistance in business management, financial recording, and digital marketing strategies.